Avaliação da chuva de sementes em áreas de restinga em diferentes estágios de regeneração - Rodrigues, Maurício Augusto [UNESP]; Paoli, Adelita Aparecida Sartori [UNESP]; Barbosa, José Marcos; dos Santos Jr., Nelson Augusto (My University, 2010)
This study was conducted in an area of restinga in the municipality of São Vicente (SP). The study aimed to evaluate the seed rain in three different conditions of regeneration. Was selected the following conditions: High Forest of Restinga in the middle stage of regeneration, an area of clearing in the same condition mentioned above and a third in early stages of regeneration. In each condition were installed 10 seed collectors made of wood and screen with 80% of shade, supported to a height of 20cm of soil. They were evaluated monthly for one year, the densities of seed deposited in the collector, these seedlings are identified and categorized based on their dispersion syndrome and successional classes. The Area of High Forest area was carried out a phytosociological survey to identify which seedlings present in the rain could be from these areas. It was found that the densities of seedlings are relatively low compared to other formations of the Atlantic rain forest, but consistent with other studies of the same type of vegetation used in the study. Regarding dispersal syndromes and successional classes, there was prevalence of the zoocoric syndrome and species of secondary successional classes. The results indicate that the area has good ability to maintain their succession dynamics.
Evaluation of seed rain in areas of restinga with differents regeneration stages
Keywords: Atlantic rain forest; Seed dispersion e restoration of degraded areas